Luminescence characteristics of Dy3+ doped Gd2O3-CaO-SiO2-B2O3 scintillating glasses - Kaewkhao J. (2017)
© 2016 The Chinese Society of Rare Earths. Glasses were prepared from the compositions of 25Gd 2 O 3 -10CaO-10SiO 2 -(55-x)B 2 O 3 -xDy 2 O 3 (where x is 0.0 mol.%-1.0 mol.%) by the conventional melt-quenching technique at 1400 °C. The results demonstrated the increase in the glass density with respect to the increase in the doping concentrations of Dy 2 O 3 . Nine absorption bands were observed. The emission spectra of the developed glass showed two strong peaks at 577 nm ( 4 F 9/2 → 6 H 13/2 ) and 482 nm ( 4 F 9/2 → 6 H 15/2 ). The highest emission intensity was observed from the developed glass prepared at 0.4 mol.% of Dy 2 O 3 , as the efficient energy transfer took place from Gd 3+ to Dy 3+ . From the X-ray induced optical luminescence, the emission spectra were identical to those from PL measurements, but with the highest intensity observed from the glass quenched at 0.45 mol.% of Dy 2 O 3 . Finally, the integral scintillation efficiency of the developed glass was determined at 27% of that of the commercially available BGO crystal.